Analisis Garis Pantai Ladong Aceh Besar Tahun 2011-2015 dengan Menggunakan Sistem Informasi Geografis - Faradila, Chasandra; Setiawan, Ichsan; Miswar, Edy (Journal of Marine and Aquatic Sciences, 2017)
The purpose of this study was to determine shoreline change along the coast of Ladong, Mesjid Raya subdistrict, Aceh Besar district, Aceh province in the 5 years period started from the year 2011, 2012, 2013, 2014 and 2015. Ground check was implemented in August 2016. This study utilized Geographic Information System technology (GIS), remote sensing and by utilizing Google Earth to capture aerial photo. The result from this research showed that each year the shoreline changes, either it was abrasion or accretion. In 2011-2012 the value of abrasion reached 1.1 ha and the value of accretion reached 0.5 ha. In 2012-2013 the value of abrasion reached 0.3 ha and the value of accretion reached 0.8 ha. In 2013-2014 the value of abrasion reached 1.2 ha and the value of accretion reached 0.2 ha. In 2014-2015 the value of abrasion reached 0.2 ha and the value of accretion reached 1.5 ha. The value of the annual abrasion average reached 0.56 ha and the value of the accretion was 0.58 ha. The largest abrasion happened in 2013-2014 which reached 1.2 ha. The total value of 5 year abrasion was 2.8 ha and the total value of accretion was recorded 2.9 ha. The process of abrasion and accretion also caused a change of the length of Ladong’s coastline every year, and the river estuary was one of the reasons that caused abrasion or accretion
Keywords: accretion; abrasion; Google earth